"I wanted to be a bride, not a wife": Accounts of child marriage in the Bedouin community in Israel. (April 2023) - Binyamini, Iris Manor; Shoshana, Avihu
This article presents a qualitative study of the experience of child marriage among Bedouin in Israel. We conducted semi-structured interviews with a convenience sample of 17 young Bedouin women, aged 17–21, who were married between the ages of 12–17. The interviewees' descriptions indicate that child marriage is a powerful cultural practice that has evolved into a "natural" and "obvious" tool for supervising girls and women. All the interviewees reported domestic violence, despair, and reported suicide attempts as a response to their existential suffering in their marriage and as an act of daily resistance to a powerful and oppressive cultural practice. These findings raise challenges in the case of global mental health interventions since these interventions not only require cultural sensitivity to avoid the constraint of Western psychiatric diagnoses and classifications, but also more critical thinking about the interactions between global and local, universalist and culturalist perspectives.